Articulating Cognitive Schemas and Metaphors of Motion in the Poem Mosafer of Sohrab Sepehri - Zohreh Niksiyar (مطالعات زبانی و بلاغی)
Cognitive linguists use metaphorical language as any form of abstract understanding and expression that is presented in the form of tangible concepts. Because they believe that human beings, in the context of their relationship with the world around them, create concepts in the form of schematics in their minds. One of these schemas is the motion schemas that the present study examined in Sohrab Sepehri's poetry. The results indicate that the symbolic and mystical poem "mosafer" is full of abstract themes and is a general schema of the concept of travel. Most of the metaphors of this poem are the type of movement used to convey the concepts of travel and they have a very important role in plotting the poet's mental images.